(3GdLHQ GdNWj hJWHjbGJg (B/s - (3SJQGfL, LGdHQJs ((3HjQhJ(B: s (3OGQ GdacQ GdYQHj(B, s, 2000)
(3MPa LGhS,fXQjI GdeYGOdGJ GdBfjI GdNWjI,GdGSbGWGJ GdeJYGeOI hGdbjeI GdUZQi,GdeMOOGJ,Gdbje GdPGJjI hGdeJLgGJ GdPGJjI,GdeUahaGJ GdeYQaI GdehLHI,GdMSGHGJ HGSJNOGe GdeUahaGJ,GdHQeLI GdNWjI hfXQjI GdeHGQjGJs
(3HHdjhZQGajG(B:(3U(B.5-8(3;GdedGMb(B:(3U(B.763-818(3;cTGa GdeUWdMGJ GdYdejI(B:889-903s
Keywords: (3GdLHQ GdNWjs